2021
DOI: 10.1093/geroni/igab046.1060
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults and Family Discord or Violence During the COVID-19 Pandemic: Results of a Canada-Wide Survey

Abstract: Child abuse and intimate partner violence rates are known to increase during and in the aftermath of disasters. Research on elder abuse during disasters, including the current pandemic, is limited. As part of an online survey that explored older Canadians’ current experiences and future care plans during the COVID-19 pandemic, we aimed to determine the prevalence, contributing factors and potential outcomes of frequent family discord involving physical violence (FFD/PV) as a proxy for elder abuse. The survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Like prior research (Alzueta et al, 2021; Yuksel et al, 2021), our findings suggest an increase in verbal and/or physical conflict during this pandemic associated with worse depression and anxiety scores. In an earlier, smaller Canadian study, we reported frequent family discord involving physical violence among 1.8% of older adults, with higher proportions among multimarginalized subgroups and strongly associated with poor mental health (Gutman et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Like prior research (Alzueta et al, 2021; Yuksel et al, 2021), our findings suggest an increase in verbal and/or physical conflict during this pandemic associated with worse depression and anxiety scores. In an earlier, smaller Canadian study, we reported frequent family discord involving physical violence among 1.8% of older adults, with higher proportions among multimarginalized subgroups and strongly associated with poor mental health (Gutman et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…In this study, 7.4% of respondents reported experiencing +VPC during the pandemic, with higher proportions among gay or bisexual men, younger age group (55–64), those with lower educational attainment, living with others, low social support and community cohesion, poor self-rated general and mental health, anxiety, depression, and those who reported abuse at core follow-up 1. Although evidence is still limited in this area, we propose that experiencing frequent family discord involving physical violence among older adults can be a proxy or precursor for abuse and neglect (Gutman et al, 2021). In our present study, multivariable logistic regression revealed that a history of psychological abuse was an independent predictor of +VPC during the pandemic (OR = 1.96, 0.95 CI = 1.40–2.74).…”
Section: Discussionmentioning
confidence: 99%